The Disclosure Effect of Sustainability Reporting and Financial Statements on Investment Efficiency: Evidence in Indonesia - Devina Rizky Amalia; Wijaya Triwacananingrum (Universitas Pasundan, 2022)
This study aims to provide empirical evidence regarding the effect of the quality of financial statements and the intensity of reporting on a company’s sustainability efforts on investment efficiency. The research was conducted on all companies listed on the Indonesia Stock Exchange (IDX) sectors in 2018–2019. This study implemented a purposive sampling technique. The population derives from 52 companies with a combined sample of 104 data, uses multiple linear regression, and performs a classical assumption test. Hypothesis testing in this study used a simultaneous significance test and partial regression test appropriately. This study found that the quality of financial reports directly affects investment efficiency. The intensity of the sustainability report does not affect the company's investment efficiency; therefore, the sustainability report does not become a reference point for making investment decisions for greater efficiency. The author concluded that non-financial information does not affect investment decisions. This research proves that public companies in Indonesia can use financial reports to affect investment efficiency, whereas sustainability reports cannot be used for this purpose.